INTRODUKSI PENGETAHUAN DAN LIMPAH KETRAMPILAN PEMBUATAN BASRENG PADA ANGGOTA POSYANDU BINAKARYA - Haetami, Kiki; Junianto (Jurnal Abdi Insani, 2024)
The government is currently very concerned about efforts to reduce and prevent stunting. Growth that is below standard when aged less than 6 years is called stunting. One program to reduce stunting is providing healthy and nutrient-dense food, namely high protein, to children in posyandu activities. Posyandu members can produce healthy and nutritious food themselves in an effort to ensure product safety and hygiene and optimize the budget. The aim of this community service is to increase the knowledge and skills of posyandu women in Binakarya Village, Garut Regency in making fried fish balls (Basreng). Basreng is a nutritious food and is liked by children. The implementation method consists of two stages, namely seminars aimed at increasing knowledge and participatory plotting to improve the skills of activity participants. The activity will take place from January 5 2023 to February 6 2023, the strategic target audience is Posyandu cadre mothers. As a result of the seminar activities that have been carried out, the seminar participants' knowledge scores about fish nutrition to prevent stunting and the stages of making fried fish meatballs have increased. The knowledge score before the seminar was 7.85 and after the seminar it was 9.95 from a maximum score of 10. The process of making fried fish meatballs carried out by activity participants during the participatory denplot went well and smoothly. The fried fish meatball product produced has an appearance that is not much different from commercial fried fish meatballs. The level of education and strong motivation of strategic target audience participants are the main factors in the success of this activity. Based on the results of the activities that have been carried out, it can be concluded that the knowledge and skills of activity participants in making fried fish meatballs have increased.